Do Combined Oculomotor and Bimanual Coordination Exercises Instantly Stabilize Balance in Athletes? - Matsuura Y; Sakairi Y; Sato H; Takiura K (Dove Medical Press, 2024)
Yuki Matsuura,1 Yosuke Sakairi,2 Haruki Sato,1 Koki Takiura3 1Cooperative Faculty of Education, Utsunomiya University, Utsunomiya, Japan; 2Faculty of Health and Sport Sciences, University of Tsukuba, Tsukuba, Japan; 3Institute for Social Innovation and Cooperation, Utsunomiya University, Utsunomiya, JapanCorrespondence: Yuki Matsuura, Cooperative Faculty of Education, Utsunomiya University, 350 Mine, Utsunomiya-City, Tochigi, 321-8505, Japan, Tel +81-28-649-5378, Email yuki-matsuura@cc.utsunomiya-u.ac.jpPurpose: This study examined the immediate effects of oculomotor and bimanual coordination exercises, as well as a combination of the two, on stability of balance in athletes.Patients and Methods: Changes in center-of-gravity sway were measured in 30 college student athletes before and after the following three exercise conditions: 1) oculomotor exercises, 2) bimanual coordination exercises, and 3) a combination of oculomotor and bimanual coordination exercises (1+2). The order of these exercises was counterbalanced.Results: The combination of exercises (condition 3) reduced large swaying during balancing and immediately increased postural stability. Moreover, the oculomotor and bimanual coordination exercises (conditions 1 and 2) immediately reduced large sway during balancing when performed independently. Thus, the present study revealed that the combination of oculomotor and bimanual coordination exercises immediately reduced accidental swaying during balancing and also improved postural stability.Conclusion: This combination could be effective as an immediate balance adjustment method for athletes.Keywords: postural stability, warming up, balance training, oculomotor exercise, bimanual coordination exercise